OPTIMASI PROSESOR DENGAN BENCHMARKING SEBAGAI APLIKASI PENGUJI PERFORMANCE CENTRAL PROSESSING UNIT (CPU) (STUDI KASUS INTEL I3, I5, I7) - Handayani, Riska Dwi; Yusnanto, Tri; Wahyudiono, Sugeng (TRANSFORMASI, 2024)
Technological developments are evolving rapidly from both performance, graphics, data transmission and so on so that we need a tool with reliable capabilities in helping better performance especially on the processing unit. In the business world, today's advances in information technology have been exploited for the smoothness of work in a field that is dominated both small and large. The method used for benchmarking is an expositions identifying against equipment and compositions a measure of a expected performance. The results of the test were carried out on the central processing unit (computer processor) on the i3 processor of 3.1 Gb, GPU 3%, Plate uses 1%, network or network usage 7.0 kbps, power usage exceptionally low. Processor i5 is 3.1 Gb and GPU 0%, Circle uses 0%, network use or network use 432 kbps and low power supply usage.Keywords: Prosesor, Benchmarking, CPU, GPU.